PENERAPAN JOYFULL LEARNING UNTUK MENINGKATKAN ANTUSIASME SISWA DALAM PEMBELAJARAN IPS DI ERA DIGITAL - Nurhayati; Septi Handayani, Rita Dwi (Program Magister Pendidikan IPS UPY, 2025)
This research aims to increase student enthusiasm through joyfull learning in social studies learning in the digital era. This research combines qualitative methods and literature studies to explore the application of joyfull learning in increasing student enthusiasm for social studies learning in the digital era. Researchers chose a qualitative approach to analyze literature related to the problems studied. The data analyzed comes from literature including reading, understanding and analyzing various written sources and books related to the issues discussed. Data collection techniques use observation, interviews and documentation. The research results show that implementing joyfull learning can increase student enthusiasm in learning social studies. This is demonstrated by combining joyfull learning methods, such as gamification, use of interactive media, and technology-based exploration, students become more active, creative, and involved in the learning process.